Poverty Linked to Government Performance: Insights from Maluku Barat Daya and Halmahera Timur, Indonesia - Gaspersz, Pauline (Populasi, 2024)
This study aims to uncover the connection between government performance and poverty in a process tracing mechanism, utilizing documentation and archival records of Maluku Barat Daya and Halmahera Timur in East Indonesia, 2016-2019. Incorporating process-tracing as the method to tracing which linkage is a new approach in poverty discourse, which is the novelty of this study. Process tracing is not without challenges, considering that it requires the presence of the expected case-specific implications of its existence, which is constrained by the data availability. However, spatially speaking, the findings of this study provide valuable insights into Indonesia’s context as an archipelago nation and can be a reference for any country facing disparity and inequality. Poor government performance lowers the quality of education and infrastructure performance through the limited number of qualified civil servants, lack of good-quality data, non-optimal budget management, and lack of accountability. Poor education resulted in low technological advances, low examination results, and few good accreditation schools. In infrastructure development, the incapability of local government to provide essential services pushed people to survive on their resources and become more vulnerable to experiencing poverty. Therefore, this research concludes that government performance influences poverty reduction through education and infrastructure performance.